Praktik Rasan Tuha pada Masyarakat Suku Komering di Kabupaten Oku Timur Perspektif Hukum Keluarga Islam - Yuliandasari, Marifa; Marwin,; Hendriyadi, (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2025)
Research was carried out with the traditional Rasan Tuha marriage practices among the Komering community in Ogan Komering Ulu Timur Regency and to assess their relevance in accordance with the principles of Islamic Family Law. The study examines the steps involved in the implementation, symbolic meanings, and socio-cultural values embedded in the practice, with an analysis of its conformity to the concept of ʿurf and the legal principle of al-ʿādatu muḥakkamah. The research employs a literature-based approach with a qualitative descriptive method and a normative perspective. Data were analyzed through content analysis to explore local cultural practices in connection with Islamic legal principles. The findings indicate that Rasan Tuha is still practiced through pre-marriage, marriage contract, and post-marriage stages, although some rituals have been simplified due to economic and efficiency considerations. The tradition continues to uphold values of deliberation, inter-family respect, and the strengthening of social bonds. From the perspective of Islamic Family Law, Rasan Tuha can be categorized as ʿurf ṣaḥīḥ, as it does not conflict with Sharia but rather supports the fulfillment of the pillars and conditions of marriage. Therefore, Rasan Tuha functions not only as a cultural heritage but also as a socio-religious instrument that reinforces family structure and aligns with Islamic principles.